Characterization of a de novo constitutional balanced translocation - Karim Zad Hagh, Javad; Saleh Gargari, Soraya; Omrani, Mir Davood (Iranian Journal of Child Neurology, 2018)
Abstract Reciprocal balanced translocations associated with clinical features are very rare. This study reports cytogenetic and molecular cytogenetic findings in a 3-year-old patient with mild developmental retardation, slight hypotone with a de novo balanced 46, XX, t(2; 11) (q33; q23) translocation. G-banded chromosomes and FISH-Analysis were used to examine the patient’s karyotype as well as her parents’. FISH-probes prepared with specific RP11-BAC clones mapped near 2q33 and 11q23 regions were used to characterize the location of the breakpoints. The FISH results revealed that one of the break points is located within the human NBEAL1-Gene locus on chromosome 2, suggesting a correlation between this gene disruption and the patient’s mild developmental retardation.